Risk Factors of Sudden Death From Subarachnoid Hemorrhage - Lindbohm, Joni Valdemar; Kaprio, Jaakko; Jousilahti, Pekka; Salomaa, Veikko; Korja, Miikka (Stroke (1970), 2017)
One in every 4 subarachnoid hemorrhage (SAH) patients dies suddenly outside hospital, but most SAH risk factor studies focus on hospitalized patients. We studied the differences in risk factors between hospitalized SAH and sudden-death SAH patients. The population-based FINRISK study cohort of 65 521 individuals was followed up for 1.52 million person-years. The Cox proportional hazards model calculated hazard ratios (HRs), with all analyses adjusted for known SAH risk factors, marital status, and socioeconomic status. A competing risks model analyzed differences in risk factors between hospitalized SAHs and sudden-death SAHs. We identified 98 sudden-death SAHs and 445 hospitalized SAHs confirmed by autopsy or by standard SAH diagnostics. Increase by 5 cigarettes smoked per day elevated sudden-death SAH risk (HR, 1.28; 95% confidence interval [CI], 1.17-1.39) more than hospitalized SAH risk (HR, 1.19; 95% CI, 1.13-1.24; =0.05 for difference). Per SD (21.4 mm Hg) increase, systolic blood pressure elevated risk of sudden-death SAH (HR, 1.34; 95% CI, 1.09-1.65) more than risk for hospitalized SAH (HR, 1.25; (95% CI, 1.12-1.38; =0.05 for difference). Participants living without a partner were at elevated risk of sudden-death SAH (HR, 2.09; 95% CI, 1.33-3.28) but not of hospitalized SAH. No sudden-death SAHs occurred in normotensive never smokers aged <50 years. Sudden-death SAH risk seems to be highest among those individuals with the most adverse risk factor profiles and among those who live without a partner, whereas it is rare among normotensive never smokers aged <50 years.